Bacteriological and Antimicrobial Susceptibility Profile in Biliary Tract Infections: A Retrospective Study - Gupta, Veenu; Gupta, Rama; Aggarwal, Manisha; Singh, Satpal; Kaur, Harpreet; Chaudhary, Jyoti; Gupta, Menal; Singla, Saurabh; Kaur, Harmandeep (Journal of Gastrointestinal Infections, 2024)
Introduction In the past few years, although there has been no change in the bacteriological profile of organisms responsible for biliary tract infections (BTIs), changes in the drug susceptibility pattern of these organisms have been reported.Material and Methods We planned a retrospective study to evaluate the microbiological profile and antibiotic susceptibility patterns of isolates from patients with BTI.The study was conducted in the Department of Microbiology over a period of 1 year. We recorded the culture positivity rates, organisms identified, and the pattern of antibiotic susceptibility.Results Out of 226 bile samples received, 60.2% samples were found to be culture positive. Most of the patients were older than 40 years. Hypertension (33.1%), diabetes (28.7%), and cardiovascular diseases (8.1%) were the common underlying diseases. Common patient symptoms were abdominal pain (77.89%), jaundice (42.24%), and fever (41.52%). Cholangitis was present in 20.6% patients. Cholelithiasis or choledocholithiasis was the most common underlying etiology (39%). A total of 142 isolates were obtained, with most patients with a predominance of gram-negative isolates. Tigecycline and aminoglycosides were found to be effective against gram-negative isolates with a susceptibility of 93.4 and 95.7%, respectively. Of the gram-negative isolates, approximately 70% were multidrug resistant (MDR), with approximately 80 and 75% being extended spectrum beta-lactamases (ESBLs) and carbapenemase producers, respectively. Enterococci were 100% susceptible to linezolid and 25% of these were vancomycin-resistant enterococci (VRE).Conclusion In summary, the predominant bacteria in our study were gram-negative bacteria that showed increased resistance to cephalosporins and carbapenems. This makes the treatment of bile duct infections increasingly difficult. A comprehensive analysis of the bacterial distribution and drug resistance profiles in patients with BTIs helps physicians to make better antibiotic policies for empiric treatment.
Keywords: gram-negative isolates; antibiotic susceptibility; bacterial profile; biliary tract infections; clinical profile